A soteriological reflection on priestly Christology from an Akan perspective - Boaheng, Isaac (Stellenbosch Theological Journal, 2023)
The priesthood of Christ forms a key foundation upon which Christian soteriology is built. In the Akan traditional community where priesthood is a common religious institution, a proper understanding of the soteriological significance of Christ’s priesthood has the potential of making the Christian faith more relevant and meaningful. Nonetheless, there is inadequate scholarly attention given to this subject from an Akan perspective. This literature-based research was, therefore, conducted to contribute to the scholarly discourse about Christian soteriology by exploring how Akan traditional priestly tradition might enhance the Akan Christian understanding of the nature and relevance of Christ’s priesthood and sacrifice based on a theological study of Hebrews 9:11–14. This text has been chosen because it gives a clear expression the biblical perspective on the priestly sacrifice of Christ.As a work in the area of Christian theology, the article does not provide detailed exegesis of the text but explores theological themes that are relevant for the Akan appreciation of the priesthood of Christ. The main argument is that since the atonement of Christ is sufficient for holistic salvation, there can be no legitimate sacrifice for salvific purposes in any society. The article contributes to the contextualization of Christian theology in the Akan/African society.